A produção escrita de alunos com deficiência intelectual no contexto da mediação em sala de aula - Silva, Camila Barreto (2012)
The present research, based on the socio-historical perspective, aimed at investigating the importance of mediation tools for the learning of written language of students with intellectual disabilities, working in partnership with colleagues without such disabilities. It also aimed at analyzing whether the mediation of knowledge of written language, held by students without intellectual disabilities, favors the evolution of psychogenetic levels of students with such disabilities, as well as investigating whether the quality of the written production of students with intellectual disabilities is modified by the mediation held by classmates without disability. The study was based on a qualitative approach, using the co-participative method through the partnership between the researcher and the teachers of these students. The study included three students with intellectual disabilities from two public schools in Fortaleza, all enrolled in elementary school, the 2nd, 3rd and 4th years. The procedures of this research involved exploratory research, the application of pre-tests and post-test and text production activities, according to different textual genres. It was performed a total of 68 production activities, involving different genres, such as letter, list , advertisement, message, directions and others. The results of this research suggest that mediation strategies held by nondisabled classmates demonstrates to be important tools for the written production of students with intellectual disabilities in the context of the classroom. The mediation strategies promoted the evolution of psychogenetic levels and the expanding of vocabulary from two of the three students who participated in the research. The mediation strategies also provided the participation of all the students in speeches / debates about the construction of their writing, often abandoning the position of a scribe –in the sense of being one that only copies.